THE PATH OF SECURITIZATION: TRANSFORMATION OF FREE PAPUA MOVEMENT (OPM) TERMINOLOGY FROM ARMED CRIMINAL GROUPS TO SEPARATIST AND TERRORIST GROUPS - Pradnyana, I Putu Hadi (UI Scholars Hub, 2023)
The purpose of this study is to analyze the pattern of securitization in Papua using the speech act framework. Regarding the response to the change in status or terminology of the Free Papua Movement or Organisasi Papua Merdeka (OPM) to the Separatist Terrorist Group. The Securitization Theory of the Copenhagen School defines security as a social construction and process, not as an objective condition. This contrasts with the traditional security studies approach which defines security in terms of the threat, use, and control of military force by state actors. This research will focus on the pattern of securitization of the Indonesian government in Papua, referring to a case study of the change in terminology or status of the OPM from the original Armed Criminal Group to the Separatist Terrorist Group. The securitization pattern analyzed will use the speech act framework from the Copenhagen School. The research method used is qualitative explanatory with the type of case study. The result of the research is that the change in the terminology of OPM to a separatist terrorist group is part of a series of securitization processes by the Indonesian government in responding to OPM, which is seen through the speech act framework. The three patterns found are political statements, political statements, and securitization statements.